Taxonomic Revision of the Subgenus Augochlora (Augochlora) Smith (Apoidea, Halictinae) in Brazil - Gonçalves, Rodrigo B.; Lepeco, Anderson (Zootaxa, 2026)
The genus Augochlora represents one of the largest and more ubiquitous groups of bees in the Neotropical region. With over 120 recognized species, it is the second most speciose in the tribe Augochlorini. Two subgenera are currently recognized: Augochlora s. str. and Oxystoglossella, with the majority of species included in the former. Herein, we revise the subgenus Augochlora (Augochlora) throughout the entirety territory of Brazil and provide identification keys to the species. We examined 5,692 specimens, and a total of 58 species are recorded for the country, of which 23 are described as new: Augochlora aguiari sp. nov., A. artemis sp. nov., A. bidentata sp. nov., A. capixaba sp. nov., A. caracensis sp. nov., A. curvinasis sp. nov., A. dryas sp. nov., A. erythrogaster sp. nov., A. flavipes sp. nov., and A. julioi sp. nov., A. hadeana sp. nov., A. phaedroscutellata sp. nov., A. rhea sp. nov., A. rhytidophora sp. nov., A. santiagoi sp. nov., A. silverai sp. nov., A. singularis sp. nov., A. solivaga sp. nov., A. tesselata sp. nov., A. tuberculata sp. nov., A. umbra sp. nov., A. vachali sp. nov., and A. xanthopoda sp. nov. Lectotypes are herein designated for Augochlora essequibensis Cockerell, 1923 and Halictus alternipes Kirby, 1890. Augochlora cephalica (Moure 1941) stat. rev. is removed from synonymy with Augochlora braziliensis (Vachal, 1911), and Augochlora essequibensis Cockerell, 1923 stat. rev. is removed from synonymy with Augochlora nigrocyanea Cockerell, 1897. Photographs of type specimens and distribution maps are provided.